2017
DOI: 10.1111/gwat.12605
|View full text |Cite
|
Sign up to set email alerts
|

Water and Salt Migration with Phase Change in Saline Soil during Freezing and Thawing Processes

Abstract: Water and salt transfer coupled with phase change may cause serious damage to engineering structures in saline soil regions. In this study, the migration of water and salt in silty clay collected from the Qinghai-Tibet Plateau is explored experimentally and numerically during freezing and thawing processes. The results revealed that there are significant differences in the variations of liquid water content and solution concentration for different initial salt contents, due to salt crystallization and dissolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…According to the survey conducted by Xinjiang Institute of Ecology and Geography, Chinese Academy of Sciences in 2014 [2], the saline-alkali cultivated land in the Xinjiang irrigation area accounts for 37.72% of the cultivated land in the irrigation area, with an average annual increase in saline-alkali cultivated land of 0.26%, with soil salinization becoming an increasingly serious problem. Freezing and thawing is a unique mechanism of soil salinization in seasonal freeze-thaw areas [3]; strong freeze-thaw action drives the water to migrate to the frozen surface of the soil surface, resulting in salt migration and accumulation from groundwater and deep soil layers to the surface layers [4]. It has been found that the rate of salt accumulation caused by soil freezing-thawing was about 30%, and the annual salt accumulation rate of submembrane drip irrigation was about 14%, in the absence of irrigation to achieve salt leaching during the non-growth period [5].…”
Section: Introductionmentioning
confidence: 99%
“…According to the survey conducted by Xinjiang Institute of Ecology and Geography, Chinese Academy of Sciences in 2014 [2], the saline-alkali cultivated land in the Xinjiang irrigation area accounts for 37.72% of the cultivated land in the irrigation area, with an average annual increase in saline-alkali cultivated land of 0.26%, with soil salinization becoming an increasingly serious problem. Freezing and thawing is a unique mechanism of soil salinization in seasonal freeze-thaw areas [3]; strong freeze-thaw action drives the water to migrate to the frozen surface of the soil surface, resulting in salt migration and accumulation from groundwater and deep soil layers to the surface layers [4]. It has been found that the rate of salt accumulation caused by soil freezing-thawing was about 30%, and the annual salt accumulation rate of submembrane drip irrigation was about 14%, in the absence of irrigation to achieve salt leaching during the non-growth period [5].…”
Section: Introductionmentioning
confidence: 99%
“…Frozen soil layers sever the soil water exchange between the upper soil and groundwater before thawing is complete 9 ; therefore, soil salinisation during the spring does not depend on the groundwater level. In contrast, other studies reported that salt along with soil water moved towards the frozen layer and salinity increased in the frozen layer 10 , 11 . Then, the intensively incremental occurrence of salinity within the topsoil resembled an ‘eruption’ of salinity during the spring thawing period 12 , 13 .…”
Section: Introductionmentioning
confidence: 86%
“…However, it is not easy to quantify the relationship between soil evaporation and salt accumulation due to the complex coupling effects between soil water and salt movement under freeze-thaw conditions and the limitations of monitoring instruments. For instance, the existence of salt depresses the soil freezing point and thus influences soil water movement and evaporation (Wu, Zhou, & Jiang, 2018).…”
Section: Core Ideasmentioning
confidence: 99%